Implementation of the Spiritual Intelligence Model in Forming Noble Morals of Students in the Digital Era at Mas Miftahussalam Medan - Effendi, Elvhira; Tumiran, Tumiran; Abrianto, Danny (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology has had a significant impact on the formation of students' character, particularly in moral and spiritual aspects. This study aims to analyze the implementation of the spiritual intelligence model in shaping the noble character of students at the Miftahussalam Private Islamic Senior High School (MAS) in Medan in the digital era. The approach used was a qualitative case study. Data collection techniques included in-depth interviews, participant observation, and documentation, which were then analyzed using the Miles and Huberman interactive analysis model. The results showed that the application of spiritual intelligence values such as sincerity, patience, gratitude, and responsibility were systematically integrated through Islamic Religious Education learning, habituation of worship, and teacher role models. These values have been proven to be able to shape students' noble character as reflected in politeness, social empathy, and religious awareness. These findings emphasize the importance of strengthening the spiritual dimension in Islamic education as an effective strategy to fortify students from the negative influences of the digital era. This study provides a conceptual contribution to the development of a character education model based on spiritual values in the madrasah environment.